СОЦИАЛЬНО-КУЛЬТУРНЫЕ ФАКТОРЫ ФОРМИРОВАНИЯ МОЛОДЁЖНОЙ ЛЕКСИКИ (НА МАТЕРИАЛЕ НЕМЕЦКОГО ЯЗЫКА) (KELAJAK SARI YANGI O’ZBEKISTON: ILM-FAN, TEXNOLOGIYA VA TA’LIM, 2026)
The article is devoted to the analysis of socio-cultural factors determining the lexical composition of contemporary youth speech in Germany. Drawing on the data from the annual Youth Word of the Year competition held by Langenscheidt publishing house, as well as the research of German sociolinguists (E. Neuland, N. Bahlo), the study examines factors such as the need for self-identification, the influence of globalization and digital communication, media environment, subcultural practices, and age-related psychological traits. Special attention is paid to Anglicisms, borrowings from Turkish and Arabic, as well as regional variants of youth language. It is concluded that German youth vocabulary constitutes a dynamic system reflecting the transformation of society and the value orientations of Generations Z and Alpha.